Treponema pallidum Immunohistochemistry is positive in human intestinal Spirochetosis - Rondell P. Graham; Bita V. Naini; Sejal S. Shah; Christina A. Arnold; Rajesh Kannangai; Michael S. Torbenson; Dora M. Lam-Himlin (BMC, 2018)
Abstract Background Human intestinal spirochetosis (IS) has been recognized for decades, but whether it represents commensalism or a pathogenic process remains controversial. IS is diagnosed on routine stains with confirmation by silver stains but these stains are labor intensive and slow to read. We evaluated the Treponema pallidum immunostain as a diagnostic adjunct for IS. Methods We retrieved biopsies from 33 patients with IS for this study. Each case was tested by Warthin-Starry (WS) and T. pallidum immunohistochemistry (IHC). Species specific genotyping was performed in 3 cases. Results Patients with IS ranged from 22 to 82 years without gender predilection. IS involved normal (n = 15), and inflamed (n = 5) mucosa and colonic polyps (n = 13). Warthin-Starry and T. pallidum IHC were positive in all cases including both species of Brachyspira. Six (18%) symptomatic patients were treated for IS, and experienced resolution. In patients diagnosed with incidental IS on cancer screening (n = 5), follow up biopsies, without therapy, were negative for IS. T. pallidum IHC required 75 min less hands-on time than WS for performance and was faster to interpret. Conclusions T. pallidum IHC can be used to confirm the diagnosis of IS and is easier to perform and faster to interpret than WS.